2020
DOI: 10.1093/mnras/staa1992
|View full text |Cite
|
Sign up to set email alerts
|

NGC 474 as viewed with KCWI: diagnosing a shell galaxy

Abstract: Abstract We present new spectra obtained using Keck/KCWI and perform kinematics and stellar population analyses of the shell galaxy NGC 474, from both the galaxy centre and a region from the outer shell. We show that both regions have similarly extended star formation histories although with different stellar population properties. The central region of NGC 474 is dominated by intermediate-aged stars (8.3 ± 0.3 Gyr) with subsolar metallicity ([Z/H]=−0.24 ± 0.07 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 62 publications
0
33
1
Order By: Relevance
“…These two scenarios might be further explored using spectroscopic data of the other shells and a chemo-dynamical numerical model of the collision. We further note that Alabi et al (2020) 3 suggested a more massive progenitor, namely 10 10 M , based on a higher metallicity measurement. One would thus need observations revealing the kinematics and the stellar populations -age and metallicity -within the other shells, for instance using integral field spectroscopy.…”
Section: What Is the Progenitor Of The Shell?mentioning
confidence: 70%
“…These two scenarios might be further explored using spectroscopic data of the other shells and a chemo-dynamical numerical model of the collision. We further note that Alabi et al (2020) 3 suggested a more massive progenitor, namely 10 10 M , based on a higher metallicity measurement. One would thus need observations revealing the kinematics and the stellar populations -age and metallicity -within the other shells, for instance using integral field spectroscopy.…”
Section: What Is the Progenitor Of The Shell?mentioning
confidence: 70%
“…The stream appears to be a continuation of a linear structure stretching from the irregular shell A to the galaxy center from the south. The shell B is the one studied spectrocopically in Alabi et al (2020) and Fensch et al (2020). The galaxy NGC 474 has very bright shells up to the galactocentric distance of about 30 kpc.…”
Section: Observational Characteristics Of Ngc 474mentioning
confidence: 99%
“…The galaxy NGC 474, studied in this paper, contains some of the brightest known shells that have around 25 mag arcsec −2 in the R-band (Turnbull et al 1999). The relative faintness of shells made their spectroscopic observations in integrated starlight impossible until recently (Alabi et al 2020;Fensch et al 2020). There are however several measurements of shell kinematics using individual kinematic tracers: red-giant-branch stars of the so-called Western Shelf in M31 Andromeda galaxy (Fardal et al 2012); globular clusters (Romanowsky et al 2012) and planetary nebulae (Longobardi et al 2015) in giant elliptical galaxy M87; a combination of globular clusters, planetary nebulae, and H II regions in the Umbrella Galaxy NGC 4651 (Foster et al 2014); and RR Lyrae and blue-horizontal-branch stars in the Milky Way (Donlon et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations